Penentuan Waktu Optimal Kawin Berdasarkan Ultrasonografi Ovarium dengan Gejala Klinis Estrus pada Kambing Peranakan Etawa (DETERMINATION OF OPTIMAL MATING TIME BASED ON OVARY ULTRASONOGRAPHY WITH ESTROUS CLINICAL SYMPTOMS IN ETAWA CROSSBREED GOAT) - Satria, Yudi Eka; Yusuf, Tuty Laswardi; ., Amrozi (Jurnal Veteriner, 2016)
The aim of this study was to determine the optimal mating time in Etawa Crossbred Goat. This studyused 10 ewes, 2-3 years old, with normal estrous cycle. Initiation of estrous using Controlled Internal DrugRelease Implants (CIDR) intra vaginal and released after 12 days. The development of follicles in theovaries wasobserved using transrectal Ultrasonography (USG) every six hours until reach for 66 hoursafter CIDR removal from the vagina. Clinical signs of standing heat and vulva signs were also observedwhile under USG observation. The follicles were divided into three groups based on their diameter:small(<3 mm), medium (4-4.9 mm) and large (>5 mm) which were observed during theestrous phase. Ovulationwas predicted when large follicles (dominant follicles) havenot been seen anymore. The resulta showedthat the average follicles number in ovary after 36 hours CIDR removal were 0-1 (0.8±0.4 mm) small, 0-1(0.9±0.6 mm) medium and 1-2 (1.7±0.8 mm) large, respectively. The large follicles (7-8 mm) wereseen after36 hours CIDR removal or 24 hours after standing heat. Forty two hours after CIDR removal, the largefollicles werenot being seen anymore. It means, the ovulation were predicted in 36-42 hours after CIDRremoval or 24-30 hours after standing heat. The relationship between follicular development and clinical vulva signs (redness, swelling, mucus) revealed that the highest vulva signs (+++) wereseen in 36-42 hoursafter CIDR removal. It was concluded that the ovulation time occurred in 36-42 hours after CIDR removal,with the high intensity of vulva changes. Therefore the optimal mating time in PE 24-36 hours of standingheat or 36-42 hours after CIDR removal.
Keywords: ultrasonography; follicles; etawa crossbred goat; CIDR